PENTINGNYA BAHASA INGGRIS UNTUK ANAK–ANAK DAN REMAJA NAGARI LIMAU PURUT TAPAN - Herayati, Herayati; Irawan, Yoki; Ramdani, Ramdani (Institut Agama Islam Negeri Kerinci, 2022)
In today's modern world and the high level of competition, everyone is expected not only to have a high level of education but also to require special skills or what we usually call